Effect of Biological Organic Fertilizers and Growth Regulators for Yield of Shallot (Allium ascalonicum L.) - A. Asrijal (Agrotech Journal, 2021)
Shallot production and productivity of Indonesia is still low; thus, needs to be increased by providing biological organic fertilizers (POH) and growth regulators (ZPT). The research was carried out in the Covid-19 Pandemic Area from December 2019 to March 2020 in Talotenreng Village, Wajo Regency. The aim of this study was to determine the shallot (Allium ascalonicum L.) productivity by using POH and ZPT. Two experimental factors with the Randomized Block Design were used as method for this study. The first factor was the POH (P) concentration of 0 ml liter of water-1, 10 ml liter of water-1, 20 ml liter of water-1, and 30 liter of water-1. The second factor was the ZPT concentration (Z) of 0 ml liter of water-1, 1.0 ml liter of water-1, 1.5 ml liter of water-1, and 2.0 ml liter of water-1. The experimental results showed that the POH concentration significantly affected the weight of fresh blubs per plot and the concentration of growth regulators had a significant effect on the number of bulbs per plot and the productivity of shallots as much as 8.09 t ha-1.